The Konkans - D'Souza, Tony (New York Harcourt, 2008)
Francisco D'Sai is a firstborn son of a firstborn son--all the way back to the beginning of a long line of proud Konkans. Known as the "Jews of India," the Konkans kneeled before the Portuguese explorer Vasco da Gama's sword and before Saint Francis Xavier's cross, abandoned their Hindu traditions, and became Catholics. In 1973 Francisco's Konkan father, Lawrence, and American mother, Denise, move to Chicago, where Francisco is born. His father, who does his best to assimilate into American culture, drinks a lot and speaks little. But his mother, who served in the Peace Corps in India, and his uncle Sam (aka Samuel Erasmus D'Sai) are passionate raconteurs who do their best to preserve the family's Konkan heritage. Friends, allies, and eventually lovers, Sam and Denise feed Francisco's imagination with proud visions of India and Konkan history.
Keywords: United States -- India -- Kokna (Indic people)